Slowly progressive behavioral frontotemporal dementia syndrome in a family co‐segregating the C9orf72 expansion and a Synaptophysin mutation. Issue 3 (26th July 2021) - Prota, Joana; Rizzi, Liara; Bonadia, Luciana; de Souza, Leonardo Cruz; Caramelli, Paulo; Secolin, Rodrigo; Lopes‐Cendes, Iscia; Balthazar, Marcio L. F.
Abstract: Introduction: Synaptophysin, already related to X‐linked intellectual disability, is expressed mainly in the central nervous system. Studies in humans indicate that the downregulation of synaptophysin could be involved in the development of dementia. Our study presents the first familial case of behavioral variant frontotemporal dementia associated with the co‐occurrence of the repeat expansion in C9orf72 and a pathogenic variant in the SYP gene. Methods: Exome sequencing and repeat‐primed PCR for C9orf72 were performed for two siblings with clinical and imaging findings suggestive of slowly progressive behavioral frontotemporal dementia. Results: We found that both siblings have the hexanucleotide expansion in C9orf72 and a null variant in the SYP gene. The most affected sibling presents the putative variant in a hemizygous state. With milder symptoms, his sister has the same pathogenic variant in heterozygosis, compatible with X‐linked inheritance. Discussion: Our results strengthened previous suggestive evidence that the phenotypes associated with C9orf72 repeat expansion are variable and probably influenced by additional genetic modifiers. We hypothesized that the pathogenic variant in the SYP gene might have modified the typical phenotype associated with the C9orf72 mutation.